2009
DOI: 10.1007/s00213-008-1458-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the discriminative stimulus effects of salvinorin A and its derivatives to U69,593 and U50,488 in rats

Abstract: Background and rationale Research interests regarding the psychopharmacology of salvinorin A have been motivated by the recreational use and widespread media focus on the hallucinogenic plant, Salvia divinorum. Additionally, kappa opioid (KOP) receptor ligands may have therapeutic potential in the treatment of some neuropsychiatric conditions, including drug dependence and mood disorders. Salvinorin A is a selective KOP agonist, but only a few studies have explored the discriminative stimulus effects of this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 31 publications
2
53
1
Order By: Relevance
“…Moreover, the KOPselective antagonist norBNI completely blocked the effects of salvinorin A but had no effect by itself. The research published by Baker et al (2009) extended these findings. In this study, conducted in rats, salvinorin A, and the metabolically stabilized salvinorin A analogs salvinorin B ethoxymethyl ether and salvinorin B methoxymethyl ether substituted completely for U69,593.…”
Section: A -Opioid Receptor-mediated Effects Of Salvinorin Amentioning
confidence: 65%
“…Moreover, the KOPselective antagonist norBNI completely blocked the effects of salvinorin A but had no effect by itself. The research published by Baker et al (2009) extended these findings. In this study, conducted in rats, salvinorin A, and the metabolically stabilized salvinorin A analogs salvinorin B ethoxymethyl ether and salvinorin B methoxymethyl ether substituted completely for U69,593.…”
Section: A -Opioid Receptor-mediated Effects Of Salvinorin Amentioning
confidence: 65%
“…Discrimination trials demonstrate SA to generalize to synthetic KOR agonists with both rodents (Baker et al 2009;Wilmore-Fordham et al 2007) and primates (Butelman et al 2004(Butelman et al , 2010. These generalization effects were blocked by general opioid antagonist quadazocine (Butelman et al 2004(Butelman et al , 2010 and KOR agonist norbinaltorphimine dihydrochloride ( Wilmore-Fordham et al 2007), were not blocked by 5-HT 2 antagonist ketanserin (Butelman et al 2010), and were partially blocked by KOR antagonist 5′-guanidinonaltrindole (effective in two of three monkeys; Butelman et al 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Sal A has been found to reliably, and fully substitute for U69,593 and U50,488 in drug discriminating studies in rodents following Sal A (1 mg/kg) (ip) (Baker, Panos, Killinger, Peet, Bell, Haliw et al, 2009) and also in primates (0.001–0.032 mg/kg) (subcutaneous, sc) (Butelman, Harris, & Kreek, 2004; Butelman, Rus, Prisinzano, & Kreek, 2010). Butelman et al (2004) showed a reversal of the discriminative stimulus effects of Sal A (0.001–0.032 mg/kg) (sc) by the KOPr antagonist quadazocine but not another KOPr antagonist 5’-guanidinonaltrindole (GNTI), This may be due to different binding site for Sal A compared to traditional KOPr agonists or differences in selectivity, onset of action or pharmacokinetic properties.…”
Section: Animal Studies With Salvinorin Amentioning
confidence: 99%